Understanding the healthcare experiences of teenaged cancer patients and survivors. Issue 5 (9th October 2013) - Farjou, G.; Sinha, R.; Dix, D.; Shahbaz, A.; Klaassen, R. J.; Klassen, A. F.
Abstract Background Despite literature supporting a client and family‐centred approach to healthcare delivery in paediatric facilities, there is little information about healthcare delivery from the perspective of teenagers in the oncology setting. The objective of this study is to describe the healthcare experiences of teenagers with cancer. Methods As part of a larger study on teen‐centred care delivery in paediatric oncology, a survey included several open‐ended questions to learn about the following: (1) what teenagers liked about the cancer care they received; (2) what they disliked about the cancer care received; and (3) what they would include if they could design the perfect cancer centre for teenagers. The survey was completed by 200 teenagers (aged 12–20 years) from three paediatric hospitals in Canada. Answers to these questions were coded and developed into themes and subthemes using a thematic analysis approach. Results The number of patients providing answers was 89% for question 1, 63% for question 2 and 68.5% for question 3. Likes and dislikes were conceptualized in terms of four key themes as follows: (1) staff at the treatment centre; (2) the cancer care they received; (3) the treatment centre itself; and (4) social activities. The most common suggestions for the perfect cancer centre included having access to better entertainment, more social opportunities to interact with peers, and a more comfortable environment for themselves and their families. Conclusion Understanding teenagers' experiences in the paediatric oncology setting provides information that could be used to shape the delivery of healthcare in a way that is tailored to their needs. Further research in this area is required in order to improve existing oncology care.